Development of Teaching Materials to Support Merdeka Curriculum Learning on Solubility and Solubility Product in F Phase - Khairani Novia; Mawardi Mawardi; Okta Suryani (Jurnal Penelitian Pendidikan IPA, 2023)
By the Covid-19 pandemic which shows that students' interest in learning is decreasing and cause learning loss, the Ministry of Education and Culture is trying to restore learning given the difficulties that have arisen with launching an merdeka curriculum, the teachers and students need using learning tools as learning resources in accordance with the merdeka curriculum. This research aims to develop teaching materials to support merdeka curriculum learning on the solubility and solubility product in the F phase and reveal the validity and practicality developed. This type of research is development research using the Plomp model. This research is limited to the formation of a valid and practical prototype IV. The instrument used in this study was a questionnaire in the form of a questionnaire of validation and practicality sheets. This study conducted a validity test using the Aiken's V formula and a practicality test using the practicality using the category of practicality level adaption from Purwanto. Validation was carried out by 5 experts, namely 3 lecturers and 2 chemistry teachers. The practicality sheet was filled in by 2 chemistry teachers and 9 Phase F students at SMAN 7 Padang. Also one to one evaluation by 3 students. The validity test data processing results are 0.89 which shows the valid category. For the results of data processing for the practicality test of students, namely 88% and the teacher's practicality test is 94% which shows a very practical category. It can be concluded that teaching materials to support merdeka curriculum learning on solubility and solubility product are valid and practical